Advancing the predictive techno-economic and lifecycle assessment of prairie grass and manure co-digestion for renewable natural gas applications - Wild, Katherine; Dominguez, Juan Carlos; Moore, Lisa Schulte; Mba Wright, Mark (Frontiers in Bioengineering and Biotechnology, 2025)
Prairie grass remains an underutilized agricultural resource that could provide economic, environmental, and ecological benefits to the bioeconomy. Prairie grass and manure anaerobic digestion is a promising pathway for renewable natural gas (RNG) production, but there is limited information on how co-digestion ratios impact RNG performance. This study integrates the Anaerobic Digestion Model No. 1 (ADM1) into a techno-economic analysis (TEA) and life cycle assessment (LCA) framework to evaluate RNG production via co-digestion of prairie biomass and cattle manure. Simulations across eleven feedstock ratios showed that co-digestion can increase methane yields compared to mono-digestion of prairie biomass. The highest methane production rate (227 mL/gVS) and the lowest minimum fuel selling price (MFSP) of $41.88/GJ occurred at a 1:9 prairie-to-manure volatile solids (VS) ratio. RNG yields reached 10.1 GJ/dry tonne for this configuration—39% higher than prairie-only digestion. LCA results revealed that manure-based scenarios had the lowest global warming potential (−16.0 kg CO2-eq/GJ), while prairie-based scenarios reduced ecotoxicity (−190 kg 2,4-D-eq/GJ). Economic and environmental benefits were further improved by accounting for biochar coproducts via system expansion and allocation. Results underscore the value of ADM1 in optimizing AD system design for both profitability and sustainability.